Pendidikan Agama Islam Sebagai Strategi untuk Pembentukan Karakter Peserta Didik - Ilham Perwira; Gusmaneli Gusmaneli (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Islamic religious education is something that is important for the formation of a person's character. The development of learners' character is a major topic of discussion in the world of education, especially in Islamic religious education, but at this time it is unfortunate how increasingly unimportant the cultivation of character in students. Islamic religious education teachers are the main hope for the formation of students' character in education. In terms of character cultivation, Islamic religious education teachers play a role in developing and assisting students in forming commendable character so that there is no deviation in the morality of students. The purpose of this study is to provide guidelines for teachers in carrying out their role as Islamic religious education teachers in preventing the morality crisis in schools. In Islam, educational institutions or schools are a medium for realising education based on Islamic creed and sharia for the realisation of self-serving to Allah SWT. the attitude of deifying and developing every talent and human potential according to its fitrah (bertauhid) so that humans will avoid deviations that are not justified by religion.